Profil Pengetahuan Konseptual Siswa Kelas VII SMP Dalam Menyelesaikan Soal Persamaan Linear Satu Variabel Berdasarkan Tingkat Kemampuan Matematika - Wenny Elpriliana Suryanti; Sudarman Sudarman; Dasa Ismaimuza (Universitas Tadulako, 2015)
This research aimed to describe the profile of conceptual knowledge of seventh grade students Al-Azhar Palu of junior high school in solving linear equation-one variable (LEOV) problem. Subjects of the research were students from mathematics high ability. Data collection used mathematics achievement test, conceptual knowledge test, and interview protocol. Data of the research were analyzed by applying qualitative analysis. The result of data analysis in this research is: (1) there are by mistake in comprehending concept in classifying LEOV and non-LEOV;(2) can making a generalization by constructing a mathematical model from a story problem type; and (3)can determining equivalent equation forms, and remembering definition of order-1of LEOV and properties of LEOV.